An Evaluation of a Novel Medical Device Versus Standard Interventions in the Treatment of Tension Pneumothorax in a Swine Model (Sus scrofa). Issue 1 (28th June 2019) - Sheldon, Rowan R; Do, Woo S; Forte, Dominic M; Weiss, Jessica B; Derickson, Michael J; Eckert, Matthew J; Martin, Matthew J
Abstract: Introduction: Tension pneumothorax is a common cause of preventable death in trauma. Needle decompression is the traditional first-line intervention but has high failure rates. We sought to evaluate the effectiveness and expedience of needle thoracostomy, surgical tube thoracostomy, and Reactor™ thoracostomy – a novel spring-loaded trocar insertion device. Materials and Methods: Yorkshire swine underwent controlled thoracic insufflation to create tension pneumothorax physiology for device comparison. Additional experiments were performed by increasing insufflation pressures to achieve pulseless electrical activity. Intervention was randomized to needle thoracostomy (14 gauge), tube thoracostomy (32Fr), or Reactor™ thoracostomy (36Fr). Air leak was simulated throughout intervention with 40–80 mL/kg/min insufflation. Intrathoracic pressure monitoring and hemodynamic parameters were obtained at 1 and 5 minutes. Results: Tension physiology and tension-induced pulseless electrical activity were created in all iterations. Needle thoracostomy ( n = 28) was faster at 7.04 ± 3.04 seconds than both Reactor thoracostomy ( n = 32), 11.63 ± 5.30 ( p < 0.05) and tube thoracostomy ( n = 32), 27.06 ± 10.73 ( p < 0.01); however, Reactor™ thoracostomy was faster than tube thoracostomy ( p < 0.001). Physiological decompression was achieved in all patients treated with Reactor™ and tube thoracostomy, but only 14% of needle thoracostomy. Cardiac recovery to complete physiologic baseline occurred in only 21% (6/28) of those treated with needle thoracostomy whereas Reactor™ or tube thoracostomy demonstrated 88% (28/32) and 94% (30/32) response rates. When combined, needle thoracostomy successfully treated tension pneumothorax in only 4% (1/28) of subjects as compared to 88% (28/32) with Reactor™ thoracostomy and 94% (30/32) with tube thoracostomy ( p < 0.01). Conclusions: Needle thoracostomy provides a rapid intervention for tension pneumothorax, but is associated with unacceptably high failure rates. Reactor™ thoracostomy was effective, expedient, and may provide a useful and technically simpler first-line treatment for tension pneumothorax or tension-induced pulseless electrical activity.